TEACHER’S ROLE IN ENGLISH CLASSROOM MANAGEMENT - Rizki Khairani; Sumarsih Sumarsih (Universitas Negeri Medan, 2021)
TEACHER’S ROLE IN ENGLISH CLASSROOM MANAGEMENT *Rizki Khairani ** Prof. Dr. Sumarsih, M.Pd ABSTRACT Khairani, Rizki. Registration Number: 2161121035. Teacher’s Role In English Classroom Management. A Thesis, English Educational Program, Faculty Language and Arts, State University of Medan, 2021. This study deals with teacher roles used in English classroom management. The objectives of this study were to explain the teacher’s role and analyze how the teacher realize their role in English classroom management. A descriptive qualitative design used in this study. The data collected by observing the teacher’s role in two classes of grade ten and interview the two English teachers at SMA Negeri 11 Medan. The data analyzed based on Marmoah & Denmar theory. The findings of this study showed the first teacher did not apply teacher’s role as a motivator and evaluator. The second teacher applied seven teacher’s roles completely in teaching and learning process. It can be concluded that generally teaching and learning process of English subject in SMA Negeri 11 Medan was achieve the learning objective and have effective learning. In addition, the two teachers applied the roles of teacher as learning resource, facilitator, good manager, demonstrator, and guide while one of them did not apply the role of teacher as motivator, and evaluator. Keywords: Teacher’s Role, Classroom Management.